Pengaruh Komunikasi Internal dan Lingkungan Kerja Melalui Motivasi Bekerja pada Kepuasan Kerja Karyawan - Wanda Wulandari; Joel Faruk Sofyan (EBISMAN eBisnis Manajemen, 2026)
The media industry requires effective coordination and a supportive work environment to achieve organizational goals. However, internal communication and workplace conditions are often not optimal, affecting employee satisfaction. This study examines the effects of internal communication and the work environment on employee job satisfaction, with work motivation as a mediating variable. A quantitative causal approach was employed using an online questionnaire distributed to employees of PT Media Televisi Indonesia. From a population of 716 employees, 190 respondents were selected through disproportionate stratified random sampling. Data were analyzed to examine the direct and indirect relationships among the variables. The findings indicate that internal communication and the work environment have positive and significant effects on work motivation. Work motivation and the work environment also positively influence employee job satisfaction. Moreover, work motivation significantly mediates the relationship between internal communication and job satisfaction, suggesting that effective communication enhances satisfaction by increasing motivation. Overall, improving open communication, creating a supportive work environment, and strengthening employee motivation are essential strategies for enhancing job satisfaction, employee engagement, and long-term organizational effectiveness in the media industry.